Ablation of NLRP3 inflammasome rewires MDSC function and promotes tumor regression - Papafragkos, Iosif; Grigoriou, Maria; Boon, Louis; Kloetgen, Andreas; Hatzioannou, Aikaterini; Verginis, Panayotis (Frontiers in Immunology, 2022)
Myeloid-derived suppressor cells (MDSCs) are myeloid precursors which exert potent immunosuppressive properties in cancer. Despite the extensive knowledge on mechanisms implicated in mobilization, recruitment and function of MDSCs, still their therapeutic targeting remains an unmet need in cancer immunotherapy suggesting that unappreciated mechanisms of MDSC-mediated suppression exist. Herein, we demonstrate an important role of NLRP3 inflammasome in the functional properties of MDSCs in tumor-bearing hosts. Specifically, Nlrp3-deficient mice exhibited reduced tumor growth compared to wild-type animals and induction of robust anti-tumor immunity, accompanied by re-wiring of the MDSC compartment. Interestingly, both monocytic (M-MDSCs) and granulocytic (G-MDSCs) subsets from Nlrp3-/- mice displayed impaired suppressive activity and demonstrated significant transcriptomic alterations supporting the loss-of-function and associated with metabolic re-programming. Finally, therapeutic targeting of NLRP3 inhibited tumor development and re-programmed the MDSC compartment. These findings propose that targeting NLRP3 in MDSCs could overcome tumor-induced tolerance and may provide new checkpoints of cancer immunotherapy.